2008
DOI: 10.1111/j.1365-2761.2007.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of spinal deformity and vaccine‐induced abdominal lesions in harvest‐sized Atlantic salmon, Salmo salar L.

Abstract: Spinal deformities in Atlantic salmon, Salmo salar L., have been described as a disease of multifactorial origin for which vaccines and time of vaccination have been suggested as risk factors. A vaccine efficacy trial where spinal deformity became evident was continued by the observational study reported here. In the preharvest part of the study 17 months post-sea transfer, there was a prevalence of 11.3% spinal deformity, with deformities present only in one vaccine group indicating a strong vaccine involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 24 publications
(58 reference statements)
3
51
0
Order By: Relevance
“…A strong association between vaccine side effects and spinal deformity in harvest-sized Atlantic salmon, Salmo salar L. has also been reported [36,37] . In addition, multiple stressful handling procedures, usually occurring in intensive farming conditions of salmon aquaculture, can cause extreme mechanical loading to the spine, which may potentially induce local inflammation leading to changes in the normal pattern of growth and remodelling of the spine, that end in a spinal deformity [38][39][40] .…”
Section: Discussionmentioning
confidence: 93%
“…A strong association between vaccine side effects and spinal deformity in harvest-sized Atlantic salmon, Salmo salar L. has also been reported [36,37] . In addition, multiple stressful handling procedures, usually occurring in intensive farming conditions of salmon aquaculture, can cause extreme mechanical loading to the spine, which may potentially induce local inflammation leading to changes in the normal pattern of growth and remodelling of the spine, that end in a spinal deformity [38][39][40] .…”
Section: Discussionmentioning
confidence: 93%
“…Spinal deformities have been reported in natural fish populations (Ayed et al, 2008;Kessabi et al, 2009;Messaoudi et al, 2009a;Messaoudi et al, 2009b;Sun et al, 2009;Tutman et al, 2000) as well as in farmed fish (Aunsmo et al, 2008;Aunsmo et al, 2009;Bardon et al, 2009;Silverstone and Hammell, 2002). Whereas skeletal malformations in aquaculture appear to be related to a complex interaction of genetic, procedural and infectious/immunological factors (Aunsmo et al, 2008;Aunsmo et al, 2009;Bardon et al, 2009;Lall and Lewis-McCrea, 2007), the presence of deformities in natural populations are most likely related to pollution (Kessabi et al, 2009;Lemly, 2002;Messaoudi et al, 2009a).…”
Section: Discussionmentioning
confidence: 98%
“…Whereas skeletal malformations in aquaculture appear to be related to a complex interaction of genetic, procedural and infectious/immunological factors (Aunsmo et al, 2008;Aunsmo et al, 2009;Bardon et al, 2009;Lall and Lewis-McCrea, 2007), the presence of deformities in natural populations are most likely related to pollution (Kessabi et al, 2009;Lemly, 2002;Messaoudi et al, 2009a). Spinal deformities can be experimentally induced in fish upon exposure to different organic and inorganic substances, including metals, metalloids and organic substances like PAHs, OC and dioxins (Cachot et al, 2007;Gagnon and Rawson, 2009;Holth et al, 2008;Miller et al, 2007;Yamauchi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Deschamps et al (2008) reported vertebral abnormalities of up to 55% in some French trout farms. The cause of deformity is probably multifactoral (Aunsmo et al 2008). Although available phosphorus and vitamin levels in the diet (such as vitamins C, E and A) may be inappropriate to support normal bone development in rapidly growing Atlantic salmon (Hughes 1992, King & Lee 1993, Roberts et al 2001, Lall & Lewis-McCrea 2007, no correlation was found between vertebral abnormalities and bone condition (density or mineralization) in trout (Deschamps et al 2008).…”
Section: Introductionmentioning
confidence: 99%